2023
DOI: 10.3340/jkns.2022.0211
|View full text |Cite
|
Sign up to set email alerts
|

The Direction of Neurosurgery to Overcome the Living with COVID-19 Era : The Possibility of Telemedicine in Neurosurgery

Abstract: Objective : Due to the implementation of vaccinations and the development of therapeutic agents, the coronavirus disease 2019 (COVID-19) pandemic that started at the end of 2019 has entered a new phase. As a result, neurosurgeons should reconsider the way they treat their patients. As the COVID-19 situation prolongs, the change in neurosurgical emergency patients according to the number of confirmed cases is no longer clear. Outpatient treatment by telephone was permitted according to government policy. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…We fully agree with Lee et al 6) for the necessity to discuss the role of telemedicine in neurosurgery and the measures required to ensure its optimal use after the COVID-19 pandemic. Based on our own experience and the literature review, we think some additions would enrich the article by Lee et al 6) .…”
Section: To the Editorsupporting
confidence: 81%
See 2 more Smart Citations
“…We fully agree with Lee et al 6) for the necessity to discuss the role of telemedicine in neurosurgery and the measures required to ensure its optimal use after the COVID-19 pandemic. Based on our own experience and the literature review, we think some additions would enrich the article by Lee et al 6) .…”
Section: To the Editorsupporting
confidence: 81%
“…We found the article by Lee et al 6) , entitled "The Direction of Neurosurgery to Overcome the Living with COVID-19 Era : The Possibility of Telemedicine in Neurosurgery" published in your highly valued journal to be really intriguing.…”
Section: To the Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, many countries are also making changes to their legal systems to accommodate this new paradigm. Recently, several preliminary studies on feasibility of telemedicine have been reported according to this atmosphere [ 29 30 31 ]. The present guideline also tried to explore the potential role and direction that telemedicine may have in the field of neurooncology in the future.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 pandemic has had an impact in the neurosurgical clinical practice either in changing the way to take care of patients [ 1 , 2 ] or changing the risk of some disease like tumors or brain injuries [ 3 6 ]. During recent meetings of the European Society for Pediatric Neurosurgery (ESPN), a certain feeling about a possible change also in the epidemiology of intracranial complications of sinusitis and otitis (ICSO) started circulating based on personal anecdotal reports.…”
Section: Introductionmentioning
confidence: 99%